2018
DOI: 10.3390/ijms19030879
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Relevance of miR-17-92 Cluster and Its Paralogous miR-106b-25 and miR-106a-363 Clusters in Brain Tumors

Abstract: The fundamental function of ribonucleic acids is to transfer genetic information from DNA to protein during translation process, however, this is not the only way connecting active RNA sequences with essential biological processes. Up until now, many RNA subclasses of different size, structure, and biological function were identified. Among them, there are non-coding single-stranded microRNAs (miRNAs). This subclass comprises RNAs of 19–25 nucleotides in length that modulate the activity of well-defined coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…On the other hand, in an in vitro model of Ewing sarcoma, hsa-miR-20b, hsa-miR-106a, and hsa-miR-18b were shown to be upregulated and to promote cell growth [46]. All three paralogs were proven to act as oncogenes in several types of brain tumors, as reviewed by Gruszka et al [47]. hsa-miR-20b-3p, hsa-miR-20a-5p and hsa-miR-106a-5p were shown to be upregulated and negatively correlated with PTEN expression in primary cutaneous B-cell lymphoma patients [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in an in vitro model of Ewing sarcoma, hsa-miR-20b, hsa-miR-106a, and hsa-miR-18b were shown to be upregulated and to promote cell growth [46]. All three paralogs were proven to act as oncogenes in several types of brain tumors, as reviewed by Gruszka et al [47]. hsa-miR-20b-3p, hsa-miR-20a-5p and hsa-miR-106a-5p were shown to be upregulated and negatively correlated with PTEN expression in primary cutaneous B-cell lymphoma patients [48].…”
Section: Discussionmentioning
confidence: 98%
“…mir-106a-363 cluster is one of the two highly conserved paralogs of cluster mir-17-92; the second paralog is mir-106b-25 [44,45]. mir-106a-363, although much less thoroughly examined than mir-17-92, has been demonstrated to act in both oncogenic and tumor suppressor manner in various malignancies [46][47][48][49]. Since functional effects mediated by miRNAs are highly context-dependent (tissue-, disease-, time-specific), miRNAs having oncogenic activities in one type of cancer may act as tumor suppressors in other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dysregulation of miRNAs is implicated in various diseases, including heart disease and cancer (Kee et al, 2014;Wang et al, 2015;Yang et al, 2017). Previous studies have reported that the miR-17-92 cluster induces tumorigenesis primarily by suppressing the expression of cell cycle-and tumor suppressor-related genes (Khuu and Utheim, 2016;Gruszka and Zakrzewska, 2018). In particular, the miR-17-92 cluster was highly expressed in ESCA, and its upregulation was notably correlated with lymph node metastasis, advanced TNM stage, and poor prognosis in patients with ESCA (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we describe a novel role of miR-106a in modulating autophagy process and mycobacterial elimination in human macrophages by targeting ULK1, ATG7, and ATG16L1, which may provide a better understanding of the host innate immune responses against M. tuberculosis. miR-106a is a member of miR-17 family miRNAs, which are broadly conserved and involved in a variety of biological pathways (29,30). Evidence is mounting that miR-106a plays key regulatory roles in autophagy, especially in cancer.…”
Section: Discussionmentioning
confidence: 99%